PERANAN MEDIA SOSIAL TERHADAP PENIGKATAN OMSET UMKM (STUDI KASUS PENJUALAN PAKAIAN BEKAS DI PAJAK MELATI TG.ANOM) - Pranata.S.Pd.,M.M, Sungguh Ponten (MTU PRESS, 2023)
A case study of selling used clothes at the Tj.Anom jasmine market is the subject of this study, which aims to find out how social media affects sales turnover of monza UMKM. This study observes MSME monza traders. The research sample used was random sampling of 100 MSME traders in Pancur Batu, Deli Serdang Regency, North Sumatra. Social media (X1) as the research independent variable, and sales turnover (Y) as the research dependent variable. The use of questionnaires, interviews, and observations as data collection methods. The SPSS 26 program is used for simple linear regression data analysis. To some extent, Facebook's online entertainment t-count is 9.5. The results of the study show that social media has a value of 0.625. This means that the ability of the independent variable to explain the dependent variable is 62.5%, the remaining 37.5% is explained by other variables. simple linear regression test in this study shows a significance value of 0.000 <0.05, so it can be interpreted that the Social Media variable (X) has an effect on the Sales Turnover variable (Y) and the Correlation Coefficient value (R) is 0.529 or 52.9 meaning there is a relationship significant positive relationship between Facebook Social media and sales Turnover.